1992
DOI: 10.1016/s0294-1449(16)30232-3
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis for a two-dimensional elliptic eigenvalue problem with the exponential nonlinearity

Abstract: L'accès aux archives de la revue « Annales de l'I. H. P., section C » (http://www.elsevier.com/locate/anihpc) implique l'accord avec les conditions générales d'utilisation (http://www.numdam.org/conditions). Toute utilisation commerciale ou impression systématique est constitutive d'une infraction pénale. Toute copie ou impression de ce fichier doit contenir la présente mention de copyright. Article numérisé dans le cadre du programme Numérisation de documents anciens mathématiques http://www.numdam.org/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
144
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(155 citation statements)
references
References 17 publications
9
144
1
1
Order By: Relevance
“…In this case one has some good understanding (see [5]). In particular, when Ω = B 1 (0) and λ < 8π , there is a unique solution and as λ → 8π − , the behavior of solution set is analyzed in [19] and [23]; while λ ≥ 8π , it is known by using a Pohozaev-type identity that (1.1-2) admits no solution at all (see [20]). However, S.S.Lin [14] (see also [5], [23] and [24] for more) proved that if Ω is a suitable annulus, there are both radial and non-radial solutions for any λ > 0 .…”
Section: 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this case one has some good understanding (see [5]). In particular, when Ω = B 1 (0) and λ < 8π , there is a unique solution and as λ → 8π − , the behavior of solution set is analyzed in [19] and [23]; while λ ≥ 8π , it is known by using a Pohozaev-type identity that (1.1-2) admits no solution at all (see [20]). However, S.S.Lin [14] (see also [5], [23] and [24] for more) proved that if Ω is a suitable annulus, there are both radial and non-radial solutions for any λ > 0 .…”
Section: 2)mentioning
confidence: 99%
“…As a side-remark, we point out that following [10] and [28], Chen and Li ([7] and [8]) used the moving plane method to obtain some beautiful apriori estimates for a class of elliptic partial differential equations in 2-dimensional domains. We remark that the special and important case when K = 1 was treated by K.Nagasaki and T.Suzuki (see [23] and [19]) using another method, which may also be applied to the case where K = constant (see [27]). It is clear that our result is also true if Ω is replaced by a compact 2-dimensional Riemannian manifold (M, g) and the equation is replaced by…”
Section: 2)mentioning
confidence: 99%
“…Among others are the application of the complex function theory to the blowup analysis of the family of solutions ( [19]), and the use of the rearrangement technique relative to a round sphere for spectral analysis of the linearized operator ( [24]). Consequently, we found that the set of stationary solutions C = {(A, V)} of (1.4) is much richer than the suspected, and some members are taking significant roles in the nonstationary problem.…”
mentioning
confidence: 99%
“…Это обусловлено существенной неаналитичностью структуры максимaльного решения уравнения Лиувилля [29].…”
Section: заключениеunclassified